1986
DOI: 10.1007/bf00608213
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic efficacy of propafenone: Evaluation of effective plasma levels following single and multiple doses

Abstract: In 11 patients with stable premature ventricular beats, the kinetics of single (150 and 300 mg) and multiple (150 mg t.i.d. and 300 mg t.i.d.) oral doses of propafenone were studied with reference to arrhythmia suppression. During the acute phase detectable plasma levels of the drug were achieved only with the higher dose. In 8 out of 10 patients the antiarrhythmic effect was obtained with the 300 mg dose, which was found to predict responsiveness at steady-state. During the chronic phase, antiarrhythmic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The data of the present study confirm the nonlinear kinetics of propafenone reported previously [1,9,13,14], together with a high interindividual variability, either of propafenone concentrations or of the propafenone/5-hydroxy-propafenone ratio. This parameter was well correlated with the debrisoquine hydroxylation capacity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data of the present study confirm the nonlinear kinetics of propafenone reported previously [1,9,13,14], together with a high interindividual variability, either of propafenone concentrations or of the propafenone/5-hydroxy-propafenone ratio. This parameter was well correlated with the debrisoquine hydroxylation capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Further studies documented that its electrophysiologic effects are quite similar to those of propafenone [8], and some clues in the clinical setting also suggest a direct antiarrhythmic action of the metabolite [6]. In spite of these observations, a clear-cut demonstration of a clinical antiarrhythmic effeet of 5-hydroxy-propafenone in humans is lacking thus far.In a previous study we demonstrated a wide interindividual variation in the effective plasma levels of propafenone during chronic therapy [9]. The purpose of this study was to evaluate the concentration-effect relationship of propafenone and 5-hydroxy-propafenone in individual patients during acute testing and chronic treatment.…”
mentioning
confidence: 98%
“…In less than 10% of patients, metabolism is slow with an elimination half-life of 10–32 h because of their deficiency of CYP2D6 6 . In extensive metabolizers, propafenone also undergoes saturable presystemic biotransformation such that its bioavailability is both dose and dosage form dependent 7 , 8 , 9 , 10 . Propafenone exhibits a high degree of inter-subject variability in pharmacokinetic parameters following both single and multiple dose administration probably due to the wide range of CYP2D6 activity 11 .…”
Section: Introductionmentioning
confidence: 99%